World Views and the Concept of “Traditional” - Pierotti, Raymond (Ethnobiology Letters, 2018)
Whether individuals hold static or dynamic worldviews underlies a number of contemporary controversies, including evolution/creationist debates, the reality of climate change, and application of treaty rights by Indigenous cultures. In this last case the debate is often framed in terms of whether or not Indigenous cultures are still using traditional methods when engaged in hunting, fishing, or harvesting. My purpose is to evaluate these issues by arguing that traditional means quite different things in different cultural traditions. In Western cultures, whose roots lie in static worldviews, e.g., those put forth by Aristotle and Descartes, traditional tends to mean unchanged or perhaps timeless. In Indigenous cultures, which typically have dynamic worldviews, traditional (a Western concept), implies that technologies employed, knowledge bases, and even ceremonial practices can change when conditions require. Western thinking assumes that use of the word traditional implies that such concepts or knowledge are of the past and thus unchangeable and irrelevant to the contemporary world. Non-Indigenous investigators have contended that traditional and change are contradictory concepts and that “[traditional] carries the unacknowledged connotation that the item in question is in decline, thus in need of being preserved.” In Indigenous thinking, the term traditional implies primarily that such knowledge and its related concepts have been in existence for a lengthy time, precisely because their ability to incorporate new observations and information has kept them fresh and relevant. I discuss these alternative concepts in the contexts of treaty and land rights and contemporary conservation concepts of biodiversity.